Glucosamine Sulphate in Osteoarthritis: From Symptoms to Structure Modification - Reginster, Jean-Yves; Lecart, Marie-Paule; Bruyere, Olivier; Burlet, Nansa (Current Medicinal Chemistry - Anti-Inflammatory & Anti-Allergy Agents, 2005)
Several chemical entities have been carefully investigated for the symptomatic and structural management of osteoarthritis. The most compelling evidence of a potential for inhibiting the structural progression of osteoarthritis has been obtained with glucosamine sulfate. At any rate, this compound has clearly demonstrated a symptomatic action, mainly in osteoarthritis of the lower limbs, on pain relief and improvement of functional disability. An important issue is that all the conclusive studies with such chemical entities resulted from the use of prescription medicines and not over-thecounter pills of food supplements.
Keywords: ibuprofen